Partial descemetorhexis for delayed Descemet membrane detachment following penetrating keratoplasty, suggestion of a pathomechanism - Somar M. Hasan (American Journal of Ophthalmology Case Reports, 2021)
Purpose: to report a case of delayed Descemet membrane detachment (DMD) 45 years after penetrating keratoplasty (PK) for keratoconus and its management with a partial descemetorhexis after failed air/gas descemetopexy. A pathomechanism of DMD is proposed based on the anatomic appearance of the DMD and the success of descemetorhexis. Observations: a 60-year old male presented with acute corneal edema of his left eye 45 years after successful PK for keratoconus. Anterior segment ocular coherence tomography (AS-OCT) revealed a wide area of DMD without a visible tear. Reattachment was tried using air and gas descemetopexy with only temporary success. A partial descemetorhexis was then performed just centrally to the graft-host interface and only in the detached area followed by injection of gas bubble. Complete reattachment of Descemet membrane (DM) on the 1st post-operative day was achieved. This anatomical success was maintained 3 months post-surgery and accompanied by decrease of central corneal thickness, however with uncomplete restoration of visual acuity. Conclusion: delayed DMD following KP for keratoconus should be differentiated from acute graft rejection. It could be a result of Descemet tear, but in some cases and despite careful observation of AS-OCT no tear could be seen. In such cases, a tractional detachment of DM might be the underlying pathomechanism and descemetorhexis could help manage it. This new surgical approach might help avoid a re-keratoplasty. Importance: This is the first case report describing success of partial descemetorhexis as a surgical management option for delayed DMD and suggesting a pathogenesis based on this success. This might help avoid re-keratoplasty as a management of this rare complication.